How do electoral systems affect fiscal policy? Evidence from state and local governments, 1890 to 2005 - Patricia Funk; Christina Gathmann (Center for Economic Studies and ifo Institute (CESifo), 2010)
Using a new data set on Swiss state and local governments from 1890 to today, we analyze how the adoption of proportional representation affects fiscal policy. We show that proportional systems shift spending toward broad goods (e.g. education and welfare benefits) but decrease spending on targetable goods (e.g. roads and agricultural subsidies). Our evidence does not suggest that proportional representation increases the overall size of government. We provide new evidence on the mechanism behind these estimates. We show that proportional elections lead to better political representation of left-wing parties, which are associated with more spending. Furthermore, proportional elections lead to higher political fragmentation. However, since political fragmentation increases spending in a plurality system only, proportional elections reduce spending through its more moderate effects of fractionalized parliaments.
Keywords: H00; H10; H40; H52; H53; H72; N83; N84; 330; electoral system; public finance; political fragmentation; matching; Finanzpolitik; Teilstaat; Gemeindefinanzen; Public Choice; Wahlsystem; Schweiz